2015
DOI: 10.1063/1.4931825
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz radiation induces non-thermal structural changes associated with Fröhlich condensation in a protein crystal

Abstract: Whether long-range quantum coherent states could exist in biological systems, and beyond low-temperature regimes where quantum physics is known to be applicable, has been the subject to debate for decades. It was proposed by Fröhlich that vibrational modes within protein molecules can order and condense into a lowest-frequency vibrational mode in a process similar to Bose-Einstein condensation, and thus that macroscopic coherence could potentially be observed in biological systems. Despite the prediction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 28 publications
2
59
0
Order By: Relevance
“…It is of great importance that direct experimental evidence has been found recently for the Fröhlich condensation, as a mechanism for long range quantum coherent states of proteins and DNA in life systems (Lundholm at al., 2015) and that several advanced optical methods are available now for detection of responses and collective modes of such large biomolecules in the terahertz frequency range (Markelz, 2008), including NMRfrequencies as shown, for example, in (Ca2+)-calmodulin (Chou et al, 2001). …”
Section: Conclusion and Final Discussionmentioning
confidence: 99%
“…It is of great importance that direct experimental evidence has been found recently for the Fröhlich condensation, as a mechanism for long range quantum coherent states of proteins and DNA in life systems (Lundholm at al., 2015) and that several advanced optical methods are available now for detection of responses and collective modes of such large biomolecules in the terahertz frequency range (Markelz, 2008), including NMRfrequencies as shown, for example, in (Ca2+)-calmodulin (Chou et al, 2001). …”
Section: Conclusion and Final Discussionmentioning
confidence: 99%
“…Practical examples include quantum effects used in bird navigation [53], an explanation of how photosynthesis works [41], and possibly, even olfaction [54]. The recent discovery that lysozyme appears to demonstrate a ‘Fröhlich condensate’ [55], when combined with concept that strong electro-magnetic fields generated by mitochondria could generate ‘water order’, and thus protect against decoherence [56], is perhaps further evidence. In fact, emerging mathematical models suggest that quantum coherence can be maintained for significant periods of time, orders of magnitude longer in complex biological systems than in simple quantum systems at room temperature–in effect the system can hover in the ‘Poised Realm’ between the pure quantum and incoherent classical worlds [57].…”
Section: The Quantum Anglementioning
confidence: 99%
“…As living systems takes in energy in order to store and utilize information, so effectively using free energy to do work to create a highly ordered state that becomes more efficient and selectable by natural selection, it exports disorder, so maintaining the second law of thermodynamics. Panel ( A ) Proven and predicted quantum effects in biology from the literature: (1) life evolved because of, and has incorporated basic quantum principles, such as entanglement and tunnelling [40,74]; (2) aromatic compounds, such as tryptophan, have pi electrons that can delocalize, and can enable quantum effects [75]; (3) the first real evidence for quantum effects has come from the reliance of photosynthesis on electron tunnelling [41,42]; (4) natural selection appears to have resulted in macromolecules tuned for quantum effects suggesting universal mechanisms of charge transport in living matter [52,57]; (5) quantum beating has been detected in living systems, in particular, in photosystems, suggesting life is using quantum effects [41,43,46]; (6) over 40 years ago Fröhlich predicted that vibrational modes within proteins could condense leading to macroscopic coherence, this appears to have now been observed [55]; (7) tunnelling is now thought to be essential in both enzyme reactions and energy transfer, a quintessential component of the quantum world [4751,64,76]; (8) bacteria live in colonies, often sharing electrons with different species, and it seems that electrons are ‘transported’ over long distances–it would be surprising if tunnelling was not involved, and this sharing between archaea and bacteria is suggestive of this process being adopted in eukaryotes [47,7779]; (9) several groups now think that electron tunnelling is important in the ETC [4850]; (10) an important component of electron tunnelling is the existence of super-complexes–these now appear to exist in all orders of life, and are key in both photosynthesis and respiration [8082]; (11) ion channels play a key role in the brain, and it has been suggested that ion conduction could be described using quantum principles [65,66]; (12) alterations in electric fields surrounding the mitochondrion could play a significant role in changing ‘water order’ and be associated with disease states [56,83,84]; (13) long discussed theory that microtubules could be involved in resonant energy transfer and consciousness due to their quantum properties [45,75]; (14) the nuclear spin properties of phosphorous utilized by transfer of quantum entangled pairs across the synapse in Posner molecules, so effectively acting as a ‘qubit’ [85]. Panel ( B ) Some predictions of our own: (1) coherence could be controlled by mitochondrial potential, which is turn could enhance quantum tunnelling of electrons (as well, as possibly, other coherence-dependent functions, such as enzyme function or ion channel status)–it could be biphasic as it could enhance efficiency (high ATP, low ROS), but if too high, i...…”
Section: The Quantum Mitochondrionmentioning
confidence: 99%
“…It is now also thought that photosynthesis utilises fundamental quantum principles, involving coherence and excitons to transfer energy efficiently [38,39,41] This is especially interesting as lysozyme appears to demonstrate a Fröhlich condensate; Fröhlich suggested that terahertz radiation could be absorbed by proteins leading to them behaving as a series of coupled oscillators generating a macroscopic quantum effect [49]. If combined with the concept that the electro-magnetic (EM) fields generated by mitochondria can lead to water order, this suggests an overall protection against decoherence within the cell [50].…”
Section: The Emergence Of Quantum Biologymentioning
confidence: 99%